Evaluasi Pelaksanaan Pembelajaran Jarak Jauh Di Program Studi Pendidikan Agama Islam - Komsyah, Indah (Proceedings of Annual Conference on Islamic Educational Management, 2021)
The Covid-19 pandemic has changed face-to-face learning done online. The concept of online learning is related to distance learning. The distance learning process requires careful readiness so that learning objectives can be achieved. The purpose of this study was to determine the results of distance learning in the Islamic Religious Education study program. This study used descriptive qualitative method. The research activity was carried out in the Islamic Religious Education study program at Sayyid Ali Rahmatullah State Islamic University, Tulungagung. The research was conducted for the academic year odd academic period 2020-2021. The participants of this study were 100 students of the Islamic Religious Education study program. Data collection techniques consisted of observation and questionnaires. The data analysis process included data collection, data reduction, data presentation and drawing conclusions. The results showed that the implementation of distance learning was quite good. There are several improvements related to increasing the digital competence of lecturers so that lectures are more attractive and innovative, providing quotas and internet networks, increasing student motivation to be more active when online learning activities are carried out. The implication of the results of this study is an understanding of the concept of distance learning according to the needs and backgrounds of students.